2‐Methyltetrahydrofuran (2‐MeTHF) as a versatile green solvent for the synthesis of amphiphilic copolymers via ROP, FRP, and RAFT tandem polymerizations. Issue 11 (20th April 2020) - Englezou, Georgia; Kortsen, Kristoffer; Pacheco, Ana A. C.; Cavanagh, Robert; Lentz, Joachim C.; Krumins, Eduards; Sanders‐Velez, Carlos; Howdle, Steven M.; Nedoma, Alisyn J.; Taresco, Vincenzo
Abstract: 2‐methyltetrahydrofuran (2‐MeTHF) is a readily available, inexpensive, neoteric, bio‐based solvent. It has been adopted across a wide range of chemical processes including the batch manufacture of fine chemicals, enzymatic polycondensations and ring opening polymerizations. To reduce the environmental burden related to the synthesis of pharmaceutical‐grade polymers based on lactide and caprolactone, we envisaged the use of 2‐MeTHF. For the first time, we combined a series of metal‐free and enzymatic ROPs with free radical and controlled RAFT polymerizations (carried out separately and in tandem) in 2‐MeTHF, in order to easily tune the chemistry and the architecture of the final polymers. After a simple purification, the amphiphilic polymers were formulated into nanoparticles and tested for their cytocompatibility in three model cell lines, to assess their application as potential polymeric excipients for nanomedicines. Abstract : In this article, the suitability of 2‐MeTHF was tested as a green solvent for organo‐and enzymatically catalyzed ROP of simple diblocks and in the production of more interesting A–B–C block copolymers using a single or double catalyst system. Labileester ROP initiators HEMA and PEGMA were also used to initiate LA macromonomers. To further demonstrate the versatility of 2‐MeTHF as "multipolymerization" green solvent, the produced macromonomers were tested in FRP and RAFT tandem polymerization.